(3JbQjH GdJgPjHs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY HYV Ndbg Ydi HYV OQLGJ , hejR Hjf GdNHjK hGdWjH HGdOdGFd hGdSeGJ s
(3BNQgG (B:s
(3BNQ GdcJGH aQZ eG CUdM ef HYO ai jhe GdCQHYGA QGHY YTQ QLH GdCUH YGe SHYI hYTQjf hKeGfeGFI s
(3GfXQ GjVG Qbe (B" 185" (3HQbe (B" 1004" (3JGQjNs
(3HBNQgG NW GdeQJVi GdRHjOi UGMH JGL GdYQhSs
(3ai Chd GdfSNI CjVkG NWg HJGQjN (B1191(3g`s
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs